2023
DOI: 10.3390/foods12142729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultra–High–Pressure Sterilization in Terms of Bactericidal Effect, Qualities, and Shelf Life of ‘Xinli No. 7’ (Pyrus sinkiangensis) Pear Juice

Abstract: In this study, ultra–high–pressure sterilization (UHPS) of Xinli No. 7 juice (XL7) was explored and optimized. A challenge to implement UHPS in juice as a full alternative to thermal treatment could be represented by the adoption of a pressure level of up to 500 MPa for 20 min at one cycle followed by the packaging in aseptic conditions. It was found that UHPS and HS treatments could effectively kill the microorganisms in XL7 juice but HS treatment would inevitably lose the nutritional quality in the juice, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…The findings showed that both processing techniques effectively eradicated germs from the juice and guaranteed food safety. These findings are consistent with a study by Gan et al, who reported that bacteria could be effectively removed from pear juice using both heat treatment settings and HPP (500 MPa, 20 min) [34].…”
Section: Effects Of Tp and Pef-hpp On The Aerobic Plate Count Of Sea ...supporting
confidence: 93%
“…The findings showed that both processing techniques effectively eradicated germs from the juice and guaranteed food safety. These findings are consistent with a study by Gan et al, who reported that bacteria could be effectively removed from pear juice using both heat treatment settings and HPP (500 MPa, 20 min) [34].…”
Section: Effects Of Tp and Pef-hpp On The Aerobic Plate Count Of Sea ...supporting
confidence: 93%